Food deprivation and compensatory growth in juvenile piava, Leporinus obtusidens - Alex Pires de Oliveira NUÑER; Leonardo Schorcht Bracony Porto FERREIRA (Boletim do Instituto de Pesca)
The growth and body composition of Leporinus obtusidens juveniles (32.0 Â± 8.0 g; 137.3 Â± 11.9 mm) were evaluated under food deprivation followed by refeeding. Fish were stocked in 130-L tanks (15 fish tank-1), maintained at 26.6 Â± 0.3Â°C and fed commercial feed (42% crude protein). Four feeding regimes (days fed to apparent satiation í"” days without food) were evaluated: control (144F:0D), 1D (1F:1D), 6D (6F:6D) or 12D (12F:12D). The greatest increase in weight and growth rates were observed in control. Fish in 1D, 6D or 12D grew to 73, 64 and 65% in weight of fish in control treatment respectively. Total daily food intake was lower in 12D (1.02 Â± 0.06 g) compared to control (1.28 Â± 0.02 g). Water content of body composition was higher in control, but other parameters were not significantly different. Leporinus obtusidens showed partial compensatory growth, and the pattern of productive performance and final body composition could be adjusted to lipostatic model, since during food deprivation energy reserves are mobilized to maintain metabolism, resulting in weight loss, whereas during refeeding nutrients are used for restoration of energy reserves, slowing growth.